ARRANJO POPULACIONAL EM MILHO E SEUS REFLEXUS NA EXPRESSÃO DE COMPORTAMENTOS DE PRODUÇÃO - Silva, Adair J. d.; Matter, Edegar; Fontaniva, Cristiano; Mattioni, Tânia C.; Valentini, Ana P. F.; Wentz, Renen; Bandeira, Taiane P.; Carbonera, Roberto; Fernandes, Sandra B. V.; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo